The narrative space in the works of the Iraqi writer Muhammad Mishal: The narrations of Al-Sabari, Altaf, and Hajj Karbala are examples - Afzali, Ali; Al-Atabi, Raheem; Azeez, Estabragq (Al-Adab Journal, 2025)
Man is not separated from his space, but rather he is this space itself. The creator and artist’s exclusive sense of space may be a deep one. Hence, the relationship of space to literature is strong. Indeed, it is the essential material of novel writing in particular, as no work is devoid of evoking this component, for which the basis and noticeable support is the main component that forms its fabric. Because it is the most present and embodied component in the novel, and it is the feature that characterizes the saying of space, and in it the novelist presents a minimum of geographical indications that stimulate the reader’s imagination to discover the place depicted in the fictional story. It is one of his identities that cannot be ignored or reduced, otherwise the work will be considered incomplete and truncated. This research, based on the descriptive analytical method, addresses space in the novels of the Iraqi writer Muhammad Mashal, which are Al-Sabari, Altaf, and Hajj Karbala. It addresses the definition of space and its types: geographical, textual in its cover (writing, drawings, and colors), and semantic (political, spiritual, belonging, contemplation, and expression), benefiting from multiple examples from the three novels. The places that the writer chose in his three novels were appropriate for the events, so the spatial framework was the environment that influenced and directed the events. The more diverse the events, the more diverse the places. The characters in the novels were linked to the places in which they lived and carried out their functions and lives. They did not exist outside their own world, which was the place that contained and shaped them. The use of place, with its realistic or imaginary connotations, constitutes the narrative fabric in the three novels. The narrator was not satisfied with one place, but rather began to use multiple places to create a narrative space based on the concept of dual logic of places, as the spatial space was divided into different types, and for this reason we sometimes find one place carrying two different connotations in Novels.